Effect of Waterlogging on Carbohydrate Metabolism and the Quality of Fiber in Cotton (Gossypium hirsutum L.) - Kuai, Jie; Chen, Yinglong; Wang, Youhua; Meng, Yali; Chen, Binglin; Zhao, Wenqing; Zhou, Zhiguo (Frontiers in Plant Science, 2016)
Transient water logging occurs frequently in the Yangtze River and adversely affects cotton fiber quality. However, the carbohydrate metabolic mechanism that affects fiber quality after water logging remains undescribed. Here, the effects of five water logging levels (0, 3, 6, 9 and 12 days) were assessed during flowering and boll formation to characterize the carbohydrates, enzymes and genes that affect the fiber quality of cotton after waterlogging. The cellulose and sucrose contents of cotton fibers were significantly decreased after water logging for 6 (WL6), 9 (WL9) and 12 d (WL12), although these properties were unaffected after 3 (WL3) and 6 days at the fruiting branch 14-15 (FB14-15). Sucrose phosphate synthase (SPS) was the most sensitive to water logging among the enzymes tested. SPS activity was decreased by water logging at FB6-7, whereas it was significantly enhanced under WL3-6 at FB10-15. Water logging down-regulated the expression of fiber invertase at 10 days post anthesis (DPA), whereas that of expansin, β-1,4-glucanase and endoxyloglucan transferase (XET) was up-regulated with increasing water logging time. Increased mRNA levels and activities of fiber SuSy at each fruiting branch indicated that SuSy was the main enzyme responsible for sucrose degradation because it was markedly induced by water logging and was active even when water logging was discontinued. We therefore concluded that the reduction in fiber sucrose and down-regulation of invertase at 10 DPA led to a markedly shorter fiber length under conditions WL6-12. Significantly decreased fiber strength at FB6-11 for WL6-12 was the result of the inhibition of cellulose synthesis and the up-regulation of expansin, β-1,4-glucanase and XET, whereas fiber strength increased under WL3-6 at FB14-15 due to the increased cellulose content of the fibers. Most of the indictors tested revealed that WL6 resulted in the best compensatory performance, whereas exposure to waterlogged conditions for more than 6 days led to an irreversible limitation in fiber development.